Investigation to improve cleaning procedure on post-mortem table from cross contamination - Kumarasamy, Prakash A/L Manickam (2020)
Post-mortem examination is a routine procedure carried out by a certified medical officer in the hospital to obtain information about the cause of death or the nature of injuries. During the post-mortem procedure, evidences are collected from the dead body and sent for laboratory analyses. After the post-mortem procedure, the post-mortem table must be washed and cleaned to ensure no contamination for the subsequent procedure. However, it is questionable on the cleanliness of the post-mortem table and the effectiveness of cleaning procedure from biological fluid contamination. The aim of this study was to investigate the effective cleaning procedure on post-mortem table from cross contamination. In this study, discarded blood samples were smeared evenly across a stainless-steel measuring 2100 × 750 × 500 mm size representing the actual post-mortem table. The blood samples on the stainless-steel sheet were cleaned at varying time elapsed such as 3 hours,12 hours, 24 hours, three days and 1week duration. Four different cleaning procedures were carried out, including water wash alone, usage of powder detergent, usage of liquid dishwasher, as well as a combination of powder detergent and household bleach. After each cleaning, the surfaces were sampled and tested with Teichmann reagent. From this study, it was found that cleaning by water wash alone was not effective, showing highest level of blood contamination as compared to other methods. Using powder detergent in combination with household bleach was the most effective and the experiment showed no cross contamination in all the tested samples. This can be concluded using powder detergent with combined of bleach can improve the cleaning methods of the post-mortem table from cross contaminations. A clean and free contamination forensic procedure is important to establish analytical result which can upheld the integrity of forensic analyses